Trego Hard White Wheat - Martin, T. Joe; Sears, Rollin G.; Shroyer, James P. (My University, 2000)
An informational publication about Trego Hard White Wheat, a new hard white winter wheat variety developed by the Kansas Agricultural Experiment Station.
L919_2000-03
Keywords: L919; Crops; L